Trait Association and their Contribution in Yield Improvement in Spring Wheat (Triticum aestivum L) - Verma, Vikas; Shukla, Rama Shankar; Pandey, Suneeta; Bagde, Vinay Prakash (International Journal of Economic Plants, 2023)
The present investigation was conducted at the Breeder Seed Production Unit, Jawaharlal Nehru Krishi Vishwa Vidyalaya, Jabalpur, M.P., India during November to April, (Rabi season), 2021 to 2022 analyse grain yield and its attributing traits of wheat by correlation and path coefficient analysis. The twenty genotypes were in randomized complete block design with three replications. The results indicated that the biological yield per plant had highly significant correlation followed by harvest index with a moderate positive value and is significant with the grain yield per plant. Similarly the analysis of direct and indirect effects shows that the plant height, flag leaf length, flag leaf width, days to 50% flowering, grains per spike, biological yield per plant, and harvest index had positive direct effect on grain yield per plant. Hence it may be considered that traits namely, plant height, flag leaf length, flag leaf width, days to 50% flowering, grains per spike, biological yield per plant, and harvest index may be utilized for yield improvement breeding strategies in wheat. However, biological yield and harvest index will be given prime importance during selection of traits, due to their significant association and having a direct or indirect effect in crop yield improvement.